A multidirectional semi‐analytical method for analysis of laterally loaded pile groups in multi‐layered elastic strata. (18th February 2016) - Tehrani, F.S.; Prezzi, M.; Salgado, R.
Summary: A semi‐analytical method for calculating the response of single piles and pile groups subjected to lateral loading is developed in this paper. Displacements anywhere in the soil domain are tied to the displacements of the piles through decay functions. The principle of virtual work and the calculus of variations are used to derive the governing differential equations that describe the response of the piles and soil. The eigenvalue method and the finite difference technique are used to solve the system of coupled differential equations for the piles and soil, respectively. The proposed method takes into account the soil surface displacement along and perpendicular to the loading direction and produces displacement fields that are very close to those produced by the finite element method but at lower computational effort. Compared with the previous method that considered only the soil displacement along the loading direction, accounting for the multi‐directional soil displacement field produces responses for the piles and soil that are closer to those approximated by the finite element method. Copyright © 2016 John Wiley & Sons, Ltd.